Distribution and Kinematics of H i through Raman He ii Spectroscopy of NGC 6302 - Seok-Jun Chang; Hee-Won Lee; Jiyu Kim; Yeon-Ho Choi (The Astrophysical Journal, 2023)
The young planetary nebula NGC 6302 is known to exhibit Raman-scattered He ii features at 6545 Å and 4851 Å. These features are formed through inelastic scattering of He ii λλ 1025 and 972 with hydrogen atoms in the ground state, for which the cross sections are 1.2 × 10 ^−21 cm ^2 and 1.4 × 10 ^−22 cm ^2 , respectively. We investigate the spectrum of NGC 6302 archived in the ESO Science Portal. Our Gaussian line-fitting analysis shows that the Raman-scattered He ii features are broader and more redshifted than the hypothetical model Raman features that would be formed in a cold static H i medium. We adopt a simple scattering geometry consisting of a compact He ii emission region surrounded by an H i medium to perform Monte Carlo simulations using the radiative transfer code STaRS. Our simulations show that the H i region is characterized by the H i column density N _H I = 3 × 10 ^21 cm ^−2 , with the random speed component v _ran = 10 km s ^−1 expanding with a speed ${v}_{\exp }=13\,km\ {{\rm{s}}}^{-1}$ from the He ii emission region. Based on our best-fit parameters, we estimate the H i mass of the neutral medium M _H I ≃ 1.0 × 10 ^−2 M _⊙ , pointing out the usefulness of Raman He ii spectroscopy as a tool to trace H i components.